Perception of the elementary mathematics teachers about assessment for learning: a case study of Sukkur IBA community colleges, Sindh, Pakistan - Sahito, Zafarullah; Özer, Özen; Abro, Ghulam A.; Junejo, Kausar A. (Frontiers in Education, 2024)
This study aims to explore the perceptions of elementary mathematics teachers about assessment for learning. The participants of this study were three elementary mathematics teachers, who have been teaching mathematics for more than five years at Sukkur IBA community colleges and schools in the province of Sindh, Pakistan. The participants were selected through purposive sampling techniques. The qualitative exploratory case study research approach was used to conduct this study. The data were gathered through semistructured interviews and observations. Experts reviewed the interview guide and observation checklist to maintain the trustworthiness of the study. The data were analyzed through thematic analysis. The findings of this study revealed that teachers have a limited capacity of understanding to explain the term assessment for learning. Moreover, the study recommends the initiation of an assessment literacy program, increasing class time, reducing the number of students per class, using moveable chairs, and making amendments to the assessment policy.